Token ring arbitration scheme for on-chip CDMA bus architectures. (December 2020) - Nikolic, Tatjana R.; Djosic, Sandra M.; Nikolic, Goran S.; Djordjevic, Goran Lj
Abstract: CDMA based on-chip interconnects have recently drawn attention due to lower variance of data transfer latency compared with the shared-bus. In this paper, we present a novel design of CDMA bus arbitration unit, which allocates codewords to system nodes and resolves destination conflicts, that is, ensures that at any time all parallel transmissions are destined to different nodes. The arbitration unit is characterized by a distributed architecture in the form of a ring composed of multiple simple ring elements, each of which is attached to one system node. In comparison with conventional centralized arbiter designs, the proposed solution improves the scalability of the CDMA bus-based multi-core SoCs, enables CDMA bus to operate at higher frequencies, and allows the implementation of more elaborated arbitration algorithms, adapted to various CDMA bus variants, with low hardware complexity. Simulation results show that the proposed distributed arbitration unit represents an efficient solution for achieving high throughput and low latency data transmission in CDMA bus-based SoCs.